2018
DOI: 10.1002/alr.22068
|View full text |Cite
|
Sign up to set email alerts
|

Are multiple sinus cultures necessary during sinus surgery for chronic rhinosinusitis?

Abstract: Background Multiple cultures are commonly obtained from different sinuses where purulence is encountered during endoscopic sinus surgery (ESS). This brings into question the utility and necessity of obtaining multiple cultures. The purpose of this study was to evaluate if multiple cultures obtained during a single case is informative in finding additional pathogens or if it is a redundant, cost-increasing practice. We hypothesized that multiple sinus cultures are necessary to identify the pathogens responsible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Studies have shown that a standard sinus culture may be a poor representation of the microbiota in chronic sinusitis . Miller and Davis demonstrated that when multiple cultures were obtained from the same patient intraoperatively, 39% of them grew different pathogens. Despite these different culture results, only 5% prompted a change in antibiotics based on sensitivities …”
mentioning
confidence: 99%
“…Studies have shown that a standard sinus culture may be a poor representation of the microbiota in chronic sinusitis . Miller and Davis demonstrated that when multiple cultures were obtained from the same patient intraoperatively, 39% of them grew different pathogens. Despite these different culture results, only 5% prompted a change in antibiotics based on sensitivities …”
mentioning
confidence: 99%
“…Thus, in vitro cultures may inadvertently bias growth to select for faster growing organisms, or those without niche or symbiotic growth needs. Additionally, standard cultures may not adequately represent the microbiome due to physical limitations in obtaining the culture; for example, Miller and Davis demonstrate significant variability in pathogens in cultures from the same patient when done via standard methods compared to those obtained intraoperatively ( Feazel et al., 2011 ; Hauser et al., 2015 ; Miller and Davis, 2018 ). Thus, it may beneficial to utilize alternative molecular methods of amplification, such as polymerase chain reaction, which can identify up to an order of magnitude more taxa that might be otherwise missed in between 25%-99% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Although the correlation of swabs between the middle meatus and maxillary sinus is well established, little research exists on how representative middle meatal swabs are of the remaining sinuses. Although not a direct comparative study, a recent retrospective study by Miller et al(124) demonstrated different pathogens in two or more…”
mentioning
confidence: 99%